A novel oxalate-based three-dimensional coordination polymer showing magnetic ordering and high proton conductivity. Issue 43 (25th October 2017) - Mon, Marta; Vallejo, Julia; Pasán, Jorge; Fabelo, Oscar; Train, Cyrille; Verdaguer, Michel; Ohkoshi, Shin-ichi; Tokoro, Hiroko; Nakagawa, Kosuke; Pardo, Emilio
Abstract : A novel example of an oxalate-based multifunctional material is reported here showing the coexistence of low-temperature magnetic ordering and high proton conductivity. Abstract : A novel three-dimensional (3D) coordination polymer with the formula (C3 N2 H5 )4 [MnCr2 (ox)6 ]·5H2 O (2 ), where ox = oxalate and C3 N2 H5 = imidazolium cation, is reported. Single crystal X-ray diffraction reveals that this porous coordination polymer adopts a chiral three-dimensional quartz-like architecture, with the guest imidazolium cations and water molecules being hosted in its pores. This novel multifunctional material exhibits both a ferromagnetic ordering at T C = 3.0 K, related to the host MnCr2 network, and high proton conductivity [1.86 × 10 −3 S cm −1 at 295 K and 88% relative humidity (RH)] due to the presence of the acidic imidazolium cations and free water molecules. The similarity of the structure of compound2 to that of the previously reported analogous compound (NH4 )4 [MnCr2 (ox)6 ]·4H2 O, (1 ), also allows us to analyse, to a certain extent, the effect of the acidity of the proton donating guest molecules on proton conduction properties.2 hosts, in one-dimensional (1D) channels, imidazolium cations, which are more acidic than the ammonium ones in1 and, as a consequence, 2 shows higher proton conduction than1, highlighting the effect of the p K a of the proton donating guest molecules on proton conductivity.